Surfside girls. The mystery at the old rancho - Dwinell, Kim (Dwinell, Kim. Surfside girls., 2019)
In this full-color graphic novel, part-time sleuths Jade and Sam encounter a ghostly resident of their Surfside, California, community who believes a real-life passerby on the beach is her father who mysteriously disappeared 200 years ago. The pair set out on a quest to solve the mystery of what happened to the girl's father. As their adventure takes them around their community, Sam and Jade manage their boy crushes and help the community stage an annual surf competition.